Optimalisasi Peran Kesbangpol dalam Menjaga Harmoni Nasional melalui Pendekatan Strategis Berbasis Analisis SWOT - Hanifah Afdisya; Syafwandi (Jurnal Riset Multidisiplin Edukasi, 2025)
Optimizing the role of the National and Political Unity Agency (Kesbangpol) is a crucial factor in maintaining national harmony and stability. This journal aims to analyze and formulate strategies to optimize the role of Kesbangpol using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. The research method used is descriptive-analytical qualitative with data collection techniques through interviews, observation, and document studies. The results identify several internal and external factors influencing Kesbangpol's performance, such as strengths in regulations and collaborative networks, weaknesses in budget and technology, opportunities in public awareness and digital support, and threats from political polarization and disinformation. Based on this analysis, four alternative strategies are formulated: SO (utilizing opportunities through strengths), WO (overcoming weaknesses to seize opportunities), ST (using strengths to counter threats), and WT (minimizing weaknesses and avoiding threats). The resulting strategic recommendations are expected to serve as a guide for Kesbangpol and stakeholders in enhancing institutional effectiveness.